EXPERIMENTAL DETERMINATION OF THE OPTIMUM CUTTING TOOL FOR CNC MILLING OF 3D PRINTED PLA PARTS - KARTAL, Fuat; KAPTAN, Arslan (International Journal of 3D Printing Technologies and Digital Industry, 2023)
The purpose of this study is to determine the most suitable cutting tool for achieving the desired diameter dimensions in parts produced using PLA material in a 3D printer. A plastic plate in the shape of a rectangular prism with dimensions of 90x40x10 mm was printed without holes with a 100% filling ratio in a 3D printer. A belt-pulley mechanism requiring bearing assembly was designed, manufactured, and tested for applicability. The study successfully identified the optimum parameters for achieving a 17 mm diameter measurement with the desired tolerance in PLA material without causing melt damage. These parameters are spindle speed of 15000 rpm, feed rate of 500 mm/min, cutting depth of 0.5 mm, minimum end mill diameter of 10 mm, and 4 cutting edges. The study also found that the morphological properties of the PLA workpiece were affected by the cutting process of different diameter milling cutters. The findings of this study can be useful for improving the accuracy and efficiency of 3D printing and CNC milling processes. This study provides important insights into the appropriate cutting tool for this process of parts produced using PLA material. The identified optimum parameters can help reduce energy-time-raw material losses and accumulation of waste PLA material, which are some of the most important problems of manufacturing with 3D printers.
Keywords: Additive manufacturing; D printing; CNC milling; PLA machining; Cutting tool selection; Mechanical Engineering; Makine Mühendisliği